Efectos de las cocinas de inducción en la calidad del producto técnico del servicio residencial - Fiallos Banda, Christian Eduardo (2015)
This thesis work presents the results of an experimental investigation of the effects that will have in the quality of product that will be provided the electricity distribution companies, by the use of induction cookers that . The experimental part was developed by laboratory tests at the Salesian Polytechnic University, for 18 days in a sample of 2 induction cookers. Descriptions of procedures and elements used to perform testing and data acquisition also included. A summary of the relevant parts of the CONELEC 004/001 Regulation in regards to the quality of product and to the limits of: voltage levels, interference and power factor, is presented. An introduction of the more relevant aspects of the energy matrix of Ecuador is made, in relation to the efficient cooking program. The most important aspects of the INEN standards regarding operation and operating practices with induction cookers is also included. Relevant information on the functioning and on the components of a induction cooking system, together with the advantages of the use of this technology, is also presented. The results of the tests were analyzed and are presented in graphical form and in comparative tables that allows to identify the effects that will be having the use of induction cookers on the quality of the product provided by the electric utilities. Relevant conclusions and recommendations are also included.